Teenagers, Social Media, and the Law: Strategies for Dealing with Delinquency in the Digital World - Isnawan, Fuadi (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
The development of technology with the times cannot be separated from one another. In addition, there is now Generation Z who is familiar with technological developments in society. The convenience of this technology encourages Generation Z teenagers to use it more in their daily lives. However, many violations of existing legal norms are committed by teenagers. Making them aware of the law is a must so that they, as the next generation, have the skills and integrity in the future. This research is focused on examining forms of violation of legal norms by adolescents on social media and the importance of legal counseling for them using social media. The results of this study are forms of violation of adolescent legal norms on social media, namely bullying, hate speech and spreading fake news. This needs to be done legal counseling so that they are aware and obey the law. Of course, this is by using social media that they are familiar with, because they use it more intensively so that it will be more effective in achieving the goals of this legal counseling